2016
DOI: 10.1002/tox.22334
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to an environmentally relevant mixture of organochlorine compounds and polychlorinated biphenyls Promotes hepatic steatosis in male Ob/Ob mice

Abstract: Hepatic steatosis is recognized as an independent risk factor for the development of cardiovascular disease. While obesity and type 2 diabetes are well-established risk factors in the development of hepatic steatosis, recent studies have revealed exposure to mixtures of persistent organic pollutants (POPs), which are environmental contaminants in various fatty foods, can promote steatosis. Thus, the present study was designed to determine if exposure to a defined mixture of prevalent polychlorinated biphenyls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 55 publications
(68 reference statements)
0
56
0
Order By: Relevance
“…Given the critical role of activation of the AGE‐RAGE axis in the pathogenesis of T2DM and cardiac remodeling, these findings demonstrate that exposure to POPs promotes cardiometabolic risk and cardiac remodeling, due as least in part to POPs‐induced activation of the AGE‐RAGE axis. In states of metabolic dysfunction such as obesity and diabetes, ROS levels become exceedingly high, and when compounded with POPs exposure, innate antioxidant defense mechanisms become overwhelmed with increased levels of ROS from the activation of RAGE/NF‐κB signaling . The following results demonstrate a potential role for AGE‐RAGE signaling in the POPs‐mediated remodeling.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Given the critical role of activation of the AGE‐RAGE axis in the pathogenesis of T2DM and cardiac remodeling, these findings demonstrate that exposure to POPs promotes cardiometabolic risk and cardiac remodeling, due as least in part to POPs‐induced activation of the AGE‐RAGE axis. In states of metabolic dysfunction such as obesity and diabetes, ROS levels become exceedingly high, and when compounded with POPs exposure, innate antioxidant defense mechanisms become overwhelmed with increased levels of ROS from the activation of RAGE/NF‐κB signaling . The following results demonstrate a potential role for AGE‐RAGE signaling in the POPs‐mediated remodeling.…”
Section: Introductionmentioning
confidence: 70%
“…In a previous a study by Mulligan et al, the experimental design and POPs mixture were reported to successfully promote NAFLD hepatic steatosis in ob / ob mice . Briefly, four‐week old male WT and ob / ob mice were randomly divided into treatment groups with 10 animals per group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we investigated the ability of quercetin, naringenin, and sesamin to affect two major drug-metabolizing enzymes CYP1A and CYP3A after exposure to a mixture of POPs relevant to human exposure scenarios. Activity of both enzymes was previously shown to be induced by the presence of POPs [22]. It is well known that CYP1A-dependent EROD activity is induced by various toxicants including polycyclic aromatic hydrocarbons (PAH), polychlorated biphenyl (PCB), or polychlorodibenzo-p-dioxine (PCDD) [2325].…”
Section: Discussionmentioning
confidence: 99%
“…In some experiments 8–10 weeks old 6N leptin-deficient, genetically obese male mice ( ob / ob , Taconic, Denmark) and their wild-type (WT) littermates were used [18]. Varying fasting glucose levels have been reported (~4.5–8.5 mM) in control, HFD and ob/ob mice [18, 2024]. The specific focus of the present study was on the effects of β-adrenergic stimulation on mitochondrial ROS production, cellular Ca 2+ handling and contractile function and we therefore decided to keep glucose concentration of the superfusing Tyrode solution standardized at 5.5 mM (see detailed composition below).…”
Section: Methodsmentioning
confidence: 99%